Designing And Implementing An Esp Course To Technology Of Communication Students. - The Case Of The Third Year Technology Of Communication Students. - Lakhdari, Slimane; Benmostefa Nawal, Nawal (جامعة الوادي - university of Eloued, 2021)
This study aims to design and implement an authentic ESP course to the enrolled students at the faculty of “Sciences and Technology” , Saida University.The current course provided to those learners does not match the students’ wants and needs. The researcher adopted a descriptive, emperical approah , using a triangulation of research tools, including a class observation, a questionnaire and a structured interview. Eventually, this study reveals a deficiency in the ESP course presented to those learners. Thus, a valuable design of an ESP course is a necessity to be adopted and implemented to meet students’ needs. Key words: ESP; needs analysis; target needs; course and syllabus design; curriculum development. ملخص باللغة العربية: تهدف هذه الدراسة إلى تصميم وتنفيذ درس إنجليزية لأغراض خاصة لطلبة كلية العلوم والتكنولوجيا بجامعة سعيدة، إن نوعية الدروس المقدمة لهؤلاء المتعلمين لا تتوافق مع احتياجات طلبة تكنولوجيا الاتصال. اعتمد الباحث دراسة وصفية، تجريبية، باستخدام ثلاثة أدوات البحث، بما في ذلك الملاحظة الصفية، استبيان ومقابلة منظمة. في نهاية المطاف ، تكشف هذه الدراسة عن نقص في جودة الدروس المقدمة لهؤلاء المتعلمين. وبالتالي ، فإن استحداث و تفعيل دروس ومنهاج انجليزية لأغراض خاصة هو ضرورة وجب اعتمادها وتنفيذها لتلبية احتياجات الطلاب. الكلمات المفتاحية: الإنجليزية لأعراض خاصة ؛ تحليل الاحتياجات ؛ الاحتياجات المستهدفة ؛ تصميم درس و منهاج ؛ تطوير المنهاج الدراسي.
Article
Keywords: needs analysis ; target needs ; course and syllabus design ; curriculum development